Projeto político-pedagógico em enunciação política: uma análise da prática discursiva docente - Albino, Ângela Cristina Alves (2010)
The present work is the result of the researcher´s inquiries about the difficulties verbalized by teachers from the municipal teaching network in Campina Grande PB when planning a political-pedagogical project for the school. Observation showed that speeches of regulation and emancipation strike the project. The regulation speech comes through normative texts and operational actions. The emancipation speech is the result of theoretical approaches produced especially when teachers are being formed. Knowing that such speeches coexist in the school everyday, the discoursive practice of the teacher was taken as the object of study. We looked back into the past to better contextualize the educational reforms within the present conjuncture of productive restructuring and reforms in the State. Traditionally we see the Nation-State aiming to establish equality through education using promises to guarantee the necessary consensus to maintain the social order . Presently the economic globalization breaks through the boundaries of the Nation-State to establish relations with the community through the financing of social politics. Within the conjuncture of crisis, external intervention, especially from the World Bank, while fulfilling a plan of financing, transfers to the school and the teachers the responsibility for the educational crisis. For an analysis of the transit between the local and the global, we prioritized decentralization and authonomy which are new meanings for the traditional principles of the liberalism equality and liberty . For the empirical research, applied at a fundamental teaching school (first and second cycles), we surveyed teachers and observed the school everyday. We based our research on Fairclough´s Discourse Analysis because of the compatibility that exists with the gramscian approach that serves as the base for our investigation. The discoursive context of the school revealed, mong other aspects, fragmentation and regulation of the teachers´ work due to the amount and duration of projects being executed; insertion of business management principles aiming to change the institution into a competitive organization ; resistence to official regulation and beliefs in the possibility of builiding up a school identity through a political-pedagogical project committed to the quality of education.